2015
DOI: 10.1016/j.mspro.2015.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of High Purity Copper in Solutions Containing NaCl, Na2SO4 and NaHCO3 at Different Temperatures

Abstract: Oxygen free copper is one of the candidate materials for the design of high level radioactive waste containers, due to its excellent resistance to generalized and localized corrosion in aqueous electrolytes; particularly in reducing environments as the ones expected in the repository site. The aim of this work is to contribute to determine the material durability from the corrosion point of view. To this purpose the anodic behavior of copper was studied in solutions with different electrolytes of interest for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
0
5
2
1
Order By: Relevance
“…Al-Khariafi 33 discussed the competition between the adsorption of halide ions and OH − on the copper surface and reported that halides with a larger ionic radius yields a lower Cu dissolution rate; although, Kong 51 proposed that the ability of halide ions to polarize copper is directly proportional to the size of the ions and a larger peak current density was observed for halides with a larger radius. In our case, E corr decreased with increasing [ − SO 4 2 ], which is in good aggrement with our observation in chloridecontaining solution, 69 but it is not in good agreement with the results of Ochoa et al, 72 whos howed that E corr increased slightly with increasing [ − SO 4 2 ]. The reason for this discrepancy could be that Ochoa et al 72 did not acquire enough data to properly define the trend; however, in this study, 60 data acquired in two runs of 30 simultaneous measurements were averaged.…”
Section: Resultscontrasting
confidence: 60%
See 2 more Smart Citations
“…Al-Khariafi 33 discussed the competition between the adsorption of halide ions and OH − on the copper surface and reported that halides with a larger ionic radius yields a lower Cu dissolution rate; although, Kong 51 proposed that the ability of halide ions to polarize copper is directly proportional to the size of the ions and a larger peak current density was observed for halides with a larger radius. In our case, E corr decreased with increasing [ − SO 4 2 ], which is in good aggrement with our observation in chloridecontaining solution, 69 but it is not in good agreement with the results of Ochoa et al, 72 whos howed that E corr increased slightly with increasing [ − SO 4 2 ]. The reason for this discrepancy could be that Ochoa et al 72 did not acquire enough data to properly define the trend; however, in this study, 60 data acquired in two runs of 30 simultaneous measurements were averaged.…”
Section: Resultscontrasting
confidence: 60%
“…In our case, E corr decreased with increasing [ − SO 4 2 ], which is in good aggrement with our observation in chloridecontaining solution, 69 but it is not in good agreement with the results of Ochoa et al, 72 whos howed that E corr increased slightly with increasing [ − SO 4 2 ]. The reason for this discrepancy could be that Ochoa et al 72 did not acquire enough data to properly define the trend; however, in this study, 60 data acquired in two runs of 30 simultaneous measurements were averaged.…”
Section: Resultscontrasting
confidence: 60%
See 1 more Smart Citation
“…The E b values were more negative at higher chloride concentrations, in keeping with the general observations of others. 18,24,28,31,40,[44][45][46][47] Starosvetsky et al 46 observed local copper activation (pitting) in lowchloride solutions, while activation extended rapidly over the whole electrode surface in high-chloride solutions; however, other researchers demonstrated that decreasing the chloride concentration improved the density and decreased the porosity of the passive film, which resulted in a higher E b .…”
Section: Resultsmentioning
confidence: 99%
“…For stainless steels, pitting corrosion is inhibited by adding sodium bicarbonate (NaHCO 3 ) or sodium carbonate (Na 2 CO 3 ) to NaCl solutions; in the presence of CO 3 2− ions, the oxide film is considered to be instantaneously repaired [27][28][29]. For copper in NaHCO 3 , the initially formed oxide film is protective [30][31][32]. Similarly, corrosion of Ni-Ti superelastic alloy may be substantially inhibited by NaHCO 3 , but its effects when added to APF solutions on corrosion behaviour are unknown.…”
Section: Introductionmentioning
confidence: 99%